ANALISIS PENGARUH SUDUT DATANG CAHAYA MATAHAHARI TERHADAP DAYA KELUARAN PANEL SURYA - Kadir, Moh. Fitran; Harun, Ervan Hasan; Ilham, Jumiati (Journal Of Renewable Energy Engineering, 2025)
Indonesia's rising energy needs push the adoption of solar energy to reduce fossil fuel use. This study analyzes how sunlight's incident angle affects the output power of polycrystalline solar panels. It also determines the optimal angle for efficiency. A quantitative experiment used two panel setups: a mobile panel set at 90° and a fixed panel that tracked natural angle changes (07:00–17:00 WITA). Over seven days in Gorontalo, voltage, current, power, light intensity, panel temperature, air temperature, and humidity were measured. Results showed that the incident angle greatly influenced output power. The mobile panel produced a maximum power of 8.13 W at an intensity of 8.7846 W/m2 (09:30). The fixed panel peaked at 6.76 W at a 69° angle (12:00). For the fixed panel, the optimal angle ranged from 50° to 70°. Efficiency dropped when panel temperature exceeded 50 °C. In general, mobile panels provided higher and more stable performance. This highlights the value of a solar tracking system or determining the optimal angle to boost efficiency and support national energy security.